Best Answer

Related Post

Spread the word

Digg this post

Bookmark to delicious

Stumble the post

Add to your technorati favourite

Subscribes to this post

2 Comments Already

mygif
Smumph45 Said,
January 28th, 2011 @12:31 am  

(-b +/- (sqrt (b^2 – 4ac))) / 2a = x

when ax^2 + bx + c = 0

so in 3x^2 – 4x – 3 = 0:

(4 +/- (sqrt (16 + 36)) / 6) = x

x = 1.87 (2dp)

x = -0.54 (2dp)

mygif
chess_is_best Said,
January 28th, 2011 @12:48 am  

I think I learned it in the 7th grade too, so you’re not alone!

ax² + bx + c = 0
x² + (b/a)x + c/a = 0
x² + (b/a)x = -c/a

Now apply something called completing the square. Take half of the coefficient of x and then square it:

(b/2a)² = b² / 4a². Now add this to both sides:

x² + (b/a)x + b²/4a² = -c/a + b²/4a²
x² + (b/a)x + b²/4a² = (b² – 4ac) / 4a²

The left-hand side is now a perfect square:

(x + b/2a)² = (b² – 4ac) / 4a²

Now square root both sides. When you do, the right side can be either positive or negative.

x + b/2a = ± ?(b² – 4ac) / 2a
x = [-b ± ?(b² - 4ac)] / 2a

Leave Your Comments Below

Please Note: All comments will be hand modified by our authors so any unsuitable comments will be removed and you comments will be appreared after approved